Identifying the optimal amorphous precursor alloy system for dual-phase nanostructure formation according to the impurity tolerance and crystallization mechanism. (September 2021) - Kong, Fengyu; Yue, Shiqiang; Li, Runxia; Wang, Anding D.; Liu, C.T.
Abstract: The amorphous precursor alloys for nanostructure with high B s always exhibit a low impurity tolerance, inhibiting mass production. Here, we comparatively studied the FeBSiCu, FeBPSiCu and FePSiCu alloy systems in Fe83 B12- x P x Si4 Cu1 ( x = 0–12) alloys made with industrial raw materials. Fully amorphous ribbons were readily prepared in the Fe83 B12 Si4 Cu1 and Fe83 P12 Si4 Cu1 alloys. It is difficult to avoid the surface crystallization induced by the impurities in Fe83 B12- x P x Si4 Cu1 ( x = 2–8) amorphous alloys with a relatively high amorphous formability. The Fe83 B12 Si4 Cu1 alloy exhibits a large crystallization temperature interval (Δ T ) which can be further widened by P micro-alloying. The macro-substitution of B by P will lead to a significant decrease of Δ T . The Δ T of the novel Fe83 P12 Si4 Cu1 alloy can be effectively widened by increasing the Fe content and microalloying of B, exhibiting a good potential for the combination of superior Δ T, AFA and impurity tolerance. The low impurity tolerance in the Fe83 B12- x P x Si4 Cu1 alloys is ascribed to the significant difference in the metallurgical properties of the Fe–B and Fe–P alloys, needing new impurity purification processes. These results will bring a new perspective to develop high B s precursor alloys and experimental references for critical industrialization. Highlights: Amorphous Fe83 B12 Si4 Cu1 and Fe83 P12 Si4 Cu1 ribbons were prepared with industrial materials. Fe83 B12- x P x Si4 Cu1 ( x = 2–8) alloys exhibit superior Δ T and AFA, but low impurity tolerance. The novel FePSiCu system alloy may combinedly have superior Δ T, AFA and impurity tolerance. Metallurgical Differences in Fe–B and Fe–P alloys lead to low impurity tolerance of FeBPSiCu alloys.